Small Molecule Chaperones for the Treatment of Gaucher Disease and GBA1-Associated Parkinson Disease - Han, Tae-Un; Sam, Richard; Sidransky, Ellen (Frontiers in Cell and Developmental Biology, 2020)
Parkinson disease, the second most common movement disorder, is a complex neurodegenerative disorder hallmarked by the accumulation of alpha-synuclein, a neural-specific small protein associated with neuronal synapses. Mutations in the glucocerebrosidase gene (GBA1), implicated in the rare, autosomal recessive lysosomal disorder Gaucher disease, are the most common known genetic risk factor for Parkinson disease. Insights into the inverse relationship between glucocerebrosidase and alpha-synuclein have led to new therapeutic approaches for the treatment of Gaucher disease and GBA1-associated Parkinson disease. Unlike the current drugs used to treat Gaucher disease, which are highly expensive and do not cross the blood-brain-barrier, new small molecules therapies, including competitive and non-competitive chaperones that enhance glucocerebrosidase levels are being developed to overcome these limitations. Some of these include iminosugars, ambroxol, other competitive glucocerebrosidase inhibitors, and non-inhibitory chaperones or activators that do not compete for the active site. These drugs, which have been shown in different disease models to increase glucocerebrosidase activity, could have potential as a therapy for Gaucher disease and GBA1- associated Parkinson disease. Some have been demonstrated to reduce α-synuclein levels in pre-clinical studies using cell-based or animal models of GBA1-associated Parkinson disease, and may also have utility for idiopathic Parkinson disease.